Telescopic model of the natural cycle of activity - Ishkov, Aleksandr (Edelweiss Applied Science and Technology, 2024)
The article deals with the telescopic model of the natural cycle of activity, reflecting the hierarchical structure of the human nervous system. The main goal of the study was to develop a model that duplicates the principle of hierarchy inherent in the nervous system and used in the “Priority” temperaments classification. The author analyzes existing activity cycle models, including the OODA cycle, D. Kolb's experience-based learning model, A. Kolb and D. Kolb's extended experience-based learning model, B. McCarthy's 4MAT model of learning styles, the Margerison-McCann model and M. Belbin's team roles. As a result, a telescoping model was developed with three links (levels of detail): a small model “2/4”, a medium model “3/8”, and a large model “4/16”. The models are oriented to tasks of different complexity: from basic analysis (model “2/4”) to a detailed approach to the management of complex processes (model “4/16”). The main advantage of the proposed telescopic model is the possibility of taking into account individual neurophysiological characteristics of workers, which increases the accuracy of predicting their behavior and the efficiency of personnel use. The use of the telescopic model of the natural cycle of activity will optimize labor processes, increase employee involvement and satisfaction.